2020
DOI: 10.2147/bctt.s242115
|View full text |Cite
|
Sign up to set email alerts
|

<p>Outcomes of Sentinel Lymph Node Biopsy Using Blue Dye Method for Early Breast Cancer – A Single-Institution Experience in the Philippines</p>

Abstract: Patients and Methods: A retrospective review was done on all patients with confirmed invasive breast carcinoma, tumor size of 5 cm or less (T1/T2), who preoperatively had no clinical signs of axillary metastasis and subsequently underwent SLNB with blue dye method from January 01, 2008 to December 31, 2017. Clinicopathologic profiles were recorded. Outcomes of patients who had SLNB only were assessed. Results: One hundred twenty-nine patients matched the inclusion criteria with a mean age of 54.3 years. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Only less than 12% of the young breast cancer patients had BCS, a rate similar to what we previously reported among early-stage breast cancer patients aged ≥18 years old in our institution. Multiple factors such as co-morbidities, education level, socio-economic and marital status, and mode of diagnosis may influence the decision to pursue BCS [ 23 ]. We also observed in our local practice that patients opt for total mastectomy because of the fear of having a second surgery for recurrence (for leaving breast tissue behind), and the additional financial burden of having to undergo adjuvant breast RT after lumpectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Only less than 12% of the young breast cancer patients had BCS, a rate similar to what we previously reported among early-stage breast cancer patients aged ≥18 years old in our institution. Multiple factors such as co-morbidities, education level, socio-economic and marital status, and mode of diagnosis may influence the decision to pursue BCS [ 23 ]. We also observed in our local practice that patients opt for total mastectomy because of the fear of having a second surgery for recurrence (for leaving breast tissue behind), and the additional financial burden of having to undergo adjuvant breast RT after lumpectomy.…”
Section: Discussionmentioning
confidence: 99%
“…3 Recent findings from two tertiary centers showed that even in early-stage patients, 74% opted for a mastectomy rather than breast conservation surgery (BCS). 7,8 Recognizing that postmastectomy patients are underrepresented in contemporary HF trials, local practitioners tend to be risk averse when considering HF to the chest wall and regional nodes. In the Philippines, as in several countries, preference for HF is reduced postmastectomy versus post-BCS.…”
Section: Physician-associated Barriersmentioning
confidence: 99%
“…Sentinel lymph node biopsy was initially performed using vital blue dyes by Morton et al, 1 but as the technique has evolved, blue dye has been coupled with radiotracers for enhanced accuracy and is now rarely used alone. 21 Sentinel lymph node biopsy with blue dye alone has shown to have sensitivity of 81 percent, [22][23][24] but when used as an adjunct to lymphoscintigraphy, provides valuable visual guidance intraoperatively and increases sensitivity. 25,26 A meta-analysis of 71 studies including 25,240 patients, in which all studies used lymphoscintigraphy and 89.1 percent of studies used blue dye as an adjunct, found a 98.1 percent rate of successfully mapped sentinel lymph nodes.…”
Section: Vital Blue Dyesmentioning
confidence: 99%